IMPLEMENTASI MODERASI BERAGAMA DI PONDOK PESANTREN DARUSSALAM AL-BANTANI DESA SUKAMAJU KECAMATAN BANTAN KABUPATEN BENGKALIS - Fitriya, Fitriya; Imaduddin, Imaduddin; Indra, Indra (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The purpose of study was to reveal the implementation of religious moderation at Darussalam Al-Bantani Islamic Boarding School, Sukamaju Village, Bantan District, Bengkalis Regency. This research is a qualitative descriptive research using library research. The results of the study stated that the Al-Bantani Islamic boarding school is a salafiyah Islamic boarding school so that it focuses on learning on the yellow books which contain aspects of faith, morals, and sharia. The implementation of religious moderation in Islamic boarding schools is through collaboration between the Islamic boarding school learning curriculum and the general curriculum required by the government. In this pesantren there is also a collaboration of pesantren activities that integrates with socio-culture such as yasinan, barzanji, istighasah, muhadarah, and sorogan. There are also activities that integrate with the development of globalization such as gardening skills and activities that integrate with the interests/talents of the students such as self-defense, scouting and hadroh. In addition, the application of religious moderation can also be seen from the behavior displayed by educators and kiai in Islamic boarding schools so that it can be reflected by the students